Macrophage Inducible C-Type Lectin As a Multifunctional Player in Immunity - Patin, Emmanuel C.; Orr, Selinda Jane; Schaible, Ulrich E. (Frontiers in Immunology, 2017)
The macrophage inducible C-type lectin (Mincle) is an innate immune receptor on myeloid cells sensing diverse entities including pathogens and damaged cells. Mincle was first described as a receptor for the mycobacterial cell wall glycolipid, trehalose-6,6'-dimycolate or cord factor, and the mammalian necrotic cell derived alarmin histone deacetylase complex unit SAP130. Upon engagement by its ligands, Mincle induces secretion of innate cytokines and other immune mediators modulating inflammation and immunity. Since its discovery more than 25 years ago, the understanding of Mincle’s immune function has made significant advances in recent years. In addition to mediating immune responses to infectious agents, Mincle has been linked to promote tumour progression, autoimmunity and sterile inflammation, however further studies are required to completely unravel the complex role of Mincle in these distinct host responses. In this review, we discuss recent findings on Mincle’s biology with an emphasis on its diverse functions in immunity.